Synthesis and Evaluation of novel oxazinyl thiazolidinone derivatives antioxidant agent as potent antidiabetic - Ramarajan Rajalakshmi , Rajavel Santhi, Thangaraj Elakkiya (International Journal of Advanced Science and Technology, 2020)
A new series of 2-(4-chlorophenyl)-3-(4-(4-chlorophenyl)-6-(9H-fluoren-7-yl)-4H-1,3-oxazin-2-yl)thiazolidin-4-one are synthesized due to its more biological activities such as antidiabetic,anti-inflammatory,antioxidant,anticancer,antimicrobial.The structure of the newly synthesized compounds established based on the spectral data and basic analysis. All the synthesized compounds have moderate activity when all the compounds subjected to antioxidant activity. Anti-diabetic screening revealed that six compounds (7m-7r) with IC50 ranging from 6.8 to 57.29 µg/ml Molecular docking studies were carried out 2HRY protein.